2021
DOI: 10.1590/0102-311x00079620
|View full text |Cite
|
Sign up to set email alerts
|

Population mobility, demographic, and environmental characteristics of dengue fever epidemics in a major city in Southeastern Brazil, 2007-2015

Abstract: Around 14% of world dengue virus (DENV) cases occur in the Americas, most of them in Brazil. While socioeconomic, environmental, and behavioral correlates have been analyzed thoroughly, the role played by population mobility on DENV epidemics, especially at the local level, remains scarce. This study assesses whether the daily pattern of population mobility is associated with DENV incidence in Campinas, a Brazilian major city with over 1.2 million inhabitants in São Paulo State. DENV notifications from 2007 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(53 reference statements)
0
4
0
1
Order By: Relevance
“…On the other hand, Johansen et al [ 23 ] described that despite the fact that most reported cases are in women, they have greater health care and seek health services more often, suggesting the hypothesis of a possible greater underreporting in men, especially of acute diseases, aligned with the vector characteristic of having higher intra and peridomicile prevalence, an environment often frequented by women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Johansen et al [ 23 ] described that despite the fact that most reported cases are in women, they have greater health care and seek health services more often, suggesting the hypothesis of a possible greater underreporting in men, especially of acute diseases, aligned with the vector characteristic of having higher intra and peridomicile prevalence, an environment often frequented by women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Special attention should be devoted to these municipalities capable of maintaining Persistent Transmission even with relatively small populations. Dengue transmission requires a pool of susceptible humans and a large and competent mosquito population [ 24 , 45 , 46 ]. Mosquito population abundance may correlate with human density since the dengue vector is an urban and domestic species [ 10 , 14 , 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the association between climatic variables and dengue transmission [ 17 , 21 , 24 , 50 , 51 ]. In Ceará, the climate characterized by extended dry seasons may explain the presence of few municipalities with Persistent Transmission profiles, because low humidity and very high temperatures (on average 30°C) negatively influence the vector’s biological cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foi constatado um alto grau de heterogeneidade das medidas de associação na metanálise, de modo que variáveis geográficas e socioeconômicas foram introduzidas no modelo definitivo para a avaliação, mas que, todavia, não causaram alterações relevantes no modelo. Isso leva à possibilidade de que variáveis explicativas de diferenças entre as microrregiões podem estar relacionadas a questões como efetividade de campanhas de educação e prevenção contra a dengue, tipo de urbanização, distribuição espacial de moradias, padrão de residência e mobilidade populacional, fenômenos já descritos na literatura com o potencial afetar a incidência da dengue 37,38 . Entretanto, essas variáveis são de difícil mensuração ou não estão disponíveis em todas as microrregiões analisadas.…”
Section: Variáveisunclassified